2004
DOI: 10.1111/j.1365-2214.2004.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender in discourse behaviour in parent–child dyads: a literature review

Abstract: The paper concludes with a discussion of research designs which might allow further differentiation between existing theoretical accounts of early gender socialization through language.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 68 publications
(107 reference statements)
0
11
1
Order By: Relevance
“…Contrary to our hypotheses, both mothers and fathers talked more with sons than daughters. These results do not support earlier findings that mothers talk more with daughters than sons and that fathers talk more with sons than daughters (for a review, see Lanvers 2004; nor that mothers talk to children more than do fathers . Much of the prior research that examines mother-father differences has been conducted with very young children.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Contrary to our hypotheses, both mothers and fathers talked more with sons than daughters. These results do not support earlier findings that mothers talk more with daughters than sons and that fathers talk more with sons than daughters (for a review, see Lanvers 2004; nor that mothers talk to children more than do fathers . Much of the prior research that examines mother-father differences has been conducted with very young children.…”
Section: Discussioncontrasting
confidence: 79%
“…In one study, both boys and girls observed in same-age peer interactions used more affiliative speech with same-gender peers than in cross-gender interactions (Leman et al 2005), and in another, both boys and girls used a more affiliative style when the conversational partner was female (Leaper et al 1999). The most consistent findings of studies examining sex of child differences in parent speech are that mothers talk more with daughters than with sons and show more differentiation in their speech with daughters and sons than fathers do (Lanvers 2004). Because most prior studies have examined parental communication styles with infants and very young children, little is known about child gender effects on parental speech with older children.…”
Section: Introductionmentioning
confidence: 63%
“…Differences that did emerge tended to follow communal and agentic roles, with mothers encouraging more two‐way communication and using both more supportive and more negative speech, and fathers establishing norms and standards for children to follow and using more directive and informative speech (Hsieh, Chiu, & Lin, 2006; Tenenbaum & Leaper, 2002). Children were observed to talk more to mothers than to fathers, and after a communication breakdown with a parent, engaged in more elaboration with mothers than fathers (Lanvers, 2004). A brand preference study of Taiwanese children (Hsieh et al, 2006) found that mothers were more likely to influence their children's brand attitudes by encouraging them to express their opinions and communicate openly.…”
Section: Domains Revealing Evidence Of Gender Differencesmentioning
confidence: 99%
“…The MICS provides only a snapshot of how gender is implicated in parenting practices and health outcomes, but gender too develops dynamically. Under the assumption that social definitions of gender evolve over time, changes in average levels of certain individual variables likely change over time as well, so that gender-related issues become more salient with age (Lanvers, 2004). …”
Section: Strengths and Limitations Of The Mics And Country-level Measmentioning
confidence: 99%